Real time monitoring of solid waste with customized hardware and Internet of Things. (September 2022) - Joshi, Lalit Mohan; Bharti, Rajendra Kumar; Singh, Rajesh; Malik, Praveen Kumar
Highlights: WPAN and cloud-assisted architecture for real-time solid waste monitoring. Real-time implementation of proposed architecture with customized hardware. LabVIEW as datalogger for visualizing the status of the bins. Sensor data visualization on the cloud server through sensor and coordinator node. Abstract: According to the United Nations' Sustainable Development Goals (SDGs), waste collection and management are essential public services for every community and are also necessary for the protection of public health and the environment. The minimization of solid waste is possible with the integration of advanced technologies like the Internet of Things (IoT), and the cloud. In this study, WPAN and cloud-assisted architecture are proposed and implemented to real-time monitor solid waste from any remote location through Xbee communication and the internet. The customized hardware is implemented in real-time by embedding it in the bins. The customized sensor node and coordinator node which are connected with the cloud server visualize the sensor data and also enable real-time monitoring of the bins. LabVIEW data logger receives the bin status and represents the status of the bin in digital form. The sensor data is visualized on the cloud server via WPAN and internet connectivity. Graphical abstract: Image, graphical abstract